Perceived facilitators and barriers to continued enrollment in longitudinal studies of Alzheimer disease: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Gabel, Matthew; Coble, Dean W; Bollinger, Rebecca; Edwards, Dorothy Farrar; Lingler, Jennifer; Chin, Erin; Grill, Josh D; Stark, Susan
Abstract: Background: Retention of study participants is critical to the success of longitudinal studies of Alzheimer Disease (AD). A comprehensive understanding of the factors that influence retention requires knowledge of what motivates study participants to continue to participate and of the perceived challenges of participation. We conducted a survey of current participants in Alzheimer Disease Centers (ADCs) to characterize their perceived facilitators and burdens of participating in longitudinal studies of AD. Method: A 57‐item interview battery with 2 open ended questions was administered by telephone to 443 randomly selected study participants from four NIA funded ADCs. Respondents were 59% female, mean age was 73±8.5 ( 49‐95 yrs), and the mean number of years enrolled was 5.1±3.5 ( 0‐13.5 yrs). Result: Survey respondents showed strong altruistic motivation for participation. Almost all respondents (>90%) indicated they were motivated by a desire to advance AD research, to benefit society, and to benefit future generations of their families. In contrast, 5% of respondents identified money or gift cards as the reason they participate. Only a small minority of respondents registered complaints about study participation. The most common problems involved fatigue (12%) and the distance/inconvenience of travel to the study visit (11%). These response patterns were broadly consistent across gender, race, and age cohorts. Women and younger respondents were slightly more altruistic in motivation than men and older respondents. Also, African American respondents were more strongly motivated by personal benefit from the study and expressed greater concern about privacy of their personal information than other respondents. They also had lower trust in medical research. Conclusion: Retention of participants and their consistent attendance at regular visits is vital to the quality of longitudinal studies of AD. Our results indicate that, while most participants surveyed indicate an altruistic commitment to the study of AD, the organization of study visits could be improved to facilitate participation. In particular, increasing the convenience of both attending and executing the study visit would address the most common complaints. Furthermore, the retention of African Americans requires sensitivity to their relatively low trust in medical research.